Investigation of the potential beneficial effects of supplemental polyunsaturated fatty acids and glycosaminoglycans on the risk factors for calcium oxalate kidney stone formation using theoretical, experimental and human models - Gogwana, Pumeza Christine (Department of Chemistry, 2015)
Includes bibliographical references.